Barriers to medical consultation and strategies for enhancing the prevention and reporting of child abuse: a cross-sectional survey of caregivers of paediatric patients at a tertiary care center in Karachi, Pakistan - Sana Saeed; Muhammad Umer Junaid; Marib Ghulam Rasool Malik; Hareem Rauf; Muhammad Osama Khan; Kishwar Enam (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the knowledge of caregivers in a tertiary care setting about child abuse, their perception of potential barriers in the way of seeking medical advice for the victims, and to identify proposed solutions to ensure prevention and reporting of child abuse. Method: The cross-sectional study was conducted from June to December 2022 at the paediatric ward of the Aga Khan University Hospital, Karachi, and comprised caregivers who were attendants of inpatients. Data was collected using a predesigned anonymous questionnaire consisting of demographic information and 27 items that were scored on a 6-point Likert scale. Data was analysed using SPSS 20. Results: Of the 144 caregivers, 96(66.6%) were females and 48(33.3%) were males. Overall, 86(59.7%) were aged <35 years, 132(91.7%) were married, and 120(83.3%) were the admitted child’s parent. The majority of caregivers 110(76.4%) perceived themselves to possess a high level of knowledge about child abuse. Barriers identified included a lack of trust in police and medicolegal departments 136(94.4%), fear of repercussion from the suspect 120(83.3%) and lack of confidentiality of the victims’ identity 116(80.6%). The proposed solutions included spreading awareness among teachers 136(94.4%) and caregivers 131(91.0%) about timely reporting and consultation, and developing proper mechanisms to follow-up on victims 133(92.4%). There were significant associations between some demographic characteristics of the respondents and their self-perceived knowledge and perceptions (p<0.05). Conclusion: There was found a need to enhance public trust, ensure confidentiality, and fostering awareness through targeted strategies for a safer and more facilitative environment for children. Key Words: Child abuse, Abuse reporting, Awareness, Caregivers.